2007
DOI: 10.1128/mcb.02088-06
|View full text |Cite
|
Sign up to set email alerts
|

Loss of Cdc20 Causes a Securin-Dependent Metaphase Arrest in Two-Cell Mouse Embryos

Abstract: The anaphase-promoting complex/cyclosome (APC/C) is an E3 ubiquitin ligase mediating targeted proteolysis through ubiquitination of protein substrates to control the progression of mitosis. The APC/C recognizes its substrates through two adapter proteins, Cdc20 and Cdh1, which contain similar C-terminal domains composed of seven WD-40 repeats believed to be involved in interacting with their substrates. During the transition from metaphase to anaphase, APC/C-Cdc20 mediates the ubiquitination of securin and cyc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
85
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 111 publications
(89 citation statements)
references
References 31 publications
4
85
0
Order By: Relevance
“…By comparison, the duration of cyclin B1 degradation in somatic cells is about 20 minutes (Clute and Pines, 1999;Gavet and Pines, 2010). Given that in both oocytes and somatic cells this APC/C substrate loss is Cdc20 dependent (Jin et al, 2010;Li et al, 2007;Reis et al, 2007), the data collectively point towards a period of meiotic APC/C activity that lasts 10 times longer, from APC/C cdc20 activation to cytokinesis, than it does in mitosis of most cultured cell lines.…”
Section: Timing Of K-fiber Formation and Apc/c Activation In Mouse Oomentioning
confidence: 95%
“…By comparison, the duration of cyclin B1 degradation in somatic cells is about 20 minutes (Clute and Pines, 1999;Gavet and Pines, 2010). Given that in both oocytes and somatic cells this APC/C substrate loss is Cdc20 dependent (Jin et al, 2010;Li et al, 2007;Reis et al, 2007), the data collectively point towards a period of meiotic APC/C activity that lasts 10 times longer, from APC/C cdc20 activation to cytokinesis, than it does in mitosis of most cultured cell lines.…”
Section: Timing Of K-fiber Formation and Apc/c Activation In Mouse Oomentioning
confidence: 95%
“…For example, the anaphase-promoting complex/cyclosome (APC/C) is a multisubunit E3 ubiquitin ligase complex that has a central role in the degradation of CYC proteins. CELL CYCLE SWITCH52 (CCS52) and CELL CYCLE DIVISION20, which activate APC/C, have conserved functions in plants, yeast, and animals (Li et al, 2007;Kevei et al, 2011;Breuer et al, 2012;Guttery et al, 2012). Arabidopsis CCS52A proteins regulate endocycle onset and progression (Lammens et al, 2008;Larson-Rabin et al, 2009;Breuer et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…However, it is possible that BubR1 may function independently of APC/C Cdc20 to inhibit the onset of anaphase. It has recently been reported that loss of Cdc20 causes a securin-dependent metaphase arrest in mouse embryos, but a Cdc20 and securin double mutant could not maintain the metaphase arrest (34), suggesting that securin has both Cdc20-independent anddependent roles in preventing mitotic exit. In this study, our data provide compelling evidence that the mitotic checkpoint protein BubR1 forms a complex with securin, and that BubR1 contributes to the stability of securin by a Cdc20-independent interaction.…”
Section: Discussionmentioning
confidence: 99%